2019
DOI: 10.1371/journal.pgen.1007863
|View full text |Cite
|
Sign up to set email alerts
|

Diapause induces functional axonal regeneration after necrotic insult in C. elegans

Abstract: Many neurons are unable to regenerate after damage. The ability to regenerate after an insult depends on life stage, neuronal subtype, intrinsic and extrinsic factors. C. elegans is a powerful model to test the genetic and environmental factors that affect axonal regeneration after damage, since its axons can regenerate after neuronal insult. Here we demonstrate that diapause promotes the complete morphological regeneration of truncated touch receptor neuron (TRN) axons expressing a neurotoxic MEC-4(d) DEG/ENa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…Hence, we determined the response to gentle touch in worms fed the different strains to test whether morphological protection shown in Figure 1B translate into functional responses. Figure 1E shows that the number of responses in worms correlates with the morphological categories AxW and AxL, the two axonal categories defined as functional in previous work [22].…”
Section: Bacterial Diet Influences the Rate At Which Neurons Degeneratementioning
confidence: 57%
See 4 more Smart Citations
“…Hence, we determined the response to gentle touch in worms fed the different strains to test whether morphological protection shown in Figure 1B translate into functional responses. Figure 1E shows that the number of responses in worms correlates with the morphological categories AxW and AxL, the two axonal categories defined as functional in previous work [22].…”
Section: Bacterial Diet Influences the Rate At Which Neurons Degeneratementioning
confidence: 57%
“…This demonstrated that DAF-16 is required for the neuroprotection effect of the HT115 diet. Noteworthy, the daf-16 mutation completely abolished the protection of TRNs previously observed at 25°C in mec-4d background [22] in both bacteria, suggesting that the daf-16 mutation significantly lowers the threshold for neurodegenerative stimuli. The effect of increased degeneration in daf-16; mec-4d though much more dramatic in E. coli HT115 is also observed in OP50.…”
Section: E Coli Ht115 Protection Requires Daf-16 Signalingmentioning
confidence: 65%
See 3 more Smart Citations